2009
DOI: 10.1007/s10753-009-9110-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trefoil Peptide 3 on Expression of TNF-α, TLR4, and NF-κB in Trinitrobenzene Sulphonic Acid Induced Colitis Mice

Abstract: The trefoil factor (TFF) peptides are major secretory products of mucus cells of the gastrointestinal tract. There were evidences that administration of recombinant human TFF3 is effective in treatment of models of colitis, but the mechanism of the effects of rTFF3 is not fully understood. The main aims of this study is to evaluate effects of intraperitoneal injection recombinant human TFF3 on the expression of tumour necrosis factor alpha (TNF-alpha), toll-like receptor 4(TLR4), and nuclear factor kappaB (NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…A number of Lactobacillus strains up-regulate HBD-2 via induction of NF-jB, activator protein 1 (AP-1) and mitogen-activated protein kinase (MAPK) signaling pathways (224). Recently, due to TFF3 ability to inhibit TNFa production, TLR4 and NF-jB in a wellestablished model of trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice, TFF3 has been hypothesized to be a potent agent in controlling IBD (258).…”
Section: B Impairment Of Intestinal Antimicrobial Peptidesmentioning
confidence: 99%
“…A number of Lactobacillus strains up-regulate HBD-2 via induction of NF-jB, activator protein 1 (AP-1) and mitogen-activated protein kinase (MAPK) signaling pathways (224). Recently, due to TFF3 ability to inhibit TNFa production, TLR4 and NF-jB in a wellestablished model of trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice, TFF3 has been hypothesized to be a potent agent in controlling IBD (258).…”
Section: B Impairment Of Intestinal Antimicrobial Peptidesmentioning
confidence: 99%
“…Moreover in the TNBS rat model of experimental colitis, colonic mucosal expression of NF-B and TFF3 was regulated in an opposite manner during the course of the disease, with high expression of NF-B and strong reduction of TFF3 during active disease, and inversely during recovery. Improvement of colitis symptoms by topical administration of 5-aminosalicylic acid (5-ASA) alone or in combination with sodium butyrate was associated with upregulation of TFF3 and downregulation of NF-B expression [154] while daily intra-peritoneal injections of TFF3 starting one day after induction of colitis exerted a protective effect toward both microscopic and macroscopic colitisinduced mucosal injury [155]. TFF3 attenuated inflammation as shown by reduced inflammatory cells infiltration and reduced tissular TNF-levels, and downregulated NF-B mRNA and protein expression.…”
Section: Biological Therapy Based On Growth Factor Receptor Activationmentioning
confidence: 99%
“…It provides a critical interface between microorganisms and their hosts (1,33). To maintain healthy homeostasis of intestine, mammals have evolved a defensive network called innate and adaptive immune defensive systems (9,31). The innate immunity plays a central role in regulating immune responses to intestinal pathogen-derived microorganisms by recognizing the presence of specific bacterial antigens through an extensive family of pattern recognition receptors (PRRs), which are situated in intestinal epithelial cells and recognize conserved microbial molecules, called pathogen-associated molecular patterns (1,31).…”
mentioning
confidence: 99%
“…To maintain healthy homeostasis of intestine, mammals have evolved a defensive network called innate and adaptive immune defensive systems (9,31). The innate immunity plays a central role in regulating immune responses to intestinal pathogen-derived microorganisms by recognizing the presence of specific bacterial antigens through an extensive family of pattern recognition receptors (PRRs), which are situated in intestinal epithelial cells and recognize conserved microbial molecules, called pathogen-associated molecular patterns (1,31). Toll-like receptor 4 (TLR4) is a PRR that has been found in Drosophila melanogaster and mammals, and compelling research has shown that lipopolysaccharide (LPS), which is the major component of the outer membrane of gram-negative bacteria, binds to TLR4 and triggers signaling cascades mediated by myeloid differentiation factor MyD88 to activate the transcription factor NF-B and eventually results in inflammatory response (14,27).…”
mentioning
confidence: 99%